Associations between external beam radiotherapy and overall survival in patients with gallbladder cancer: A population-based study - Jiazhao Song; Jiazhao Song; Xiaoli Kang; Yupeng Di; Gang Ren; Yingjie Wang (Frontiers Media S.A., 2022)
BackgroundThere is a lack of studies regarding radiotherapy (RT) in patients with gallbladder cancer (GBC) on the survival benefit after surgery and nonsurgical treatment. Therefore, this study evaluated the impact of external beam RT on the overall survival (OS) of patients with GBC in a real-world setting.MethodsPatients with GBC enrolled from the Surveillance, Epidemiology, and End Results (SEER) database were examined through Kaplan-Meier survival curves and multivariable Cox regression analyses.ResultsA total of 7,866 patients with GBC were screened for the current analysis, of whom 2,130 (27.1%) did not undergo RT or surgery, 209 (2.7%) underwent RT, 4,511 (57.3%) underwent surgery, and 1,016 (12.9%) underwent both RT and surgery. The median OS times were 4 months, 8 months, 16 months, and 22 months (p < 0.0001). OS was significantly different between adjuvant RT (p = 0.0002) and palliative RT (p < 0.0001). Multifactorial analysis (controlling for age, sex, year of diagnosis, marital status, race, grade, and stage) showed that both adjuvant RT (surgery and adjuvant RT vs. surgery alone; HR, 0.75; 95% CI, 0.69-0.82, p < 0.001) and palliative RT (RT alone vs. no treatment; HR, 0.80; 95% CI, 0.69-0.92, p = 0.003) had a significant impact on patient OS. The results remained stable following sensitivity analyses.ConclusionThe study results indicate that adjuvant and palliative radiation treatment was associated with a survival benefit. GBC patients can derive a survival benefit from external beam RT.